To solve the equation \( a = \pi xy \) for \( y \), we start with the original equation:
\[ a = \pi xy \]
Next, we want to isolate \( y \). We'll divide both sides of the equation by \( \pi x \):
\[ y = \frac{a}{\pi x} \]
This doesn't directly match any of the provided options, but let's look at the options more closely:
- \( y = a · \pi x \)
- \( y = a + (\pi x) \)
- \( y = a - \pi x \)
- \( y = a ÷ (\pi x) \)
The fourth option, \( y = a ÷ (\pi x) \), is equivalent to our derived equation \( y = \frac{a}{\pi x} \).
Thus, the equivalent equation solved for \( y \) is:
\[ \boxed{y = a ÷ (\pi x)} \]